DEVELOPING STUDENTS' LOVE FOR THE HOMELAND THROUGH THE PHILOSOPHY OF MUHAMMAD YUSUF'S POETRY (Web of Teachers: Inderscience Research, 2025)
This article analyzes the importance of love for homeland and its role in the upbringing of young people. In particular, Muhammad Yusuf's poetry pays special attention to the issues of love for the homeland, respect for national values and understanding of the historical cultural heritage of their people. The article explores the role of the philosophy of Muhammad Yusuf's poetry in educating young people in the spirit of selflessness and patriotism. The article also analyzes the possible application of poetry in pedagogical processes and as an effective tool for educating young people. Effective ways to instill love for the homeland among students through methodological foundations and practical activities are considered.